PERUBAHAN KADAR RAFINOSA, GLUKOSA, MANOSA, ARABINOSA DAN SUKROSA WHEAT POLLARD AKIBAT LAMA STEAM DAN PENAMBAHAN AIR YANG BERBEDA - Bambang Sulistiyanto; Sri Kismiati; Cahya Setya Utama (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
Wheat pollard is a waste of the wheat industry and many contain non starch polisacharida (NSP) that interfere with the chicken digestive tract. NSP in wheat pollard can be removed by heating, so it can be used by microbes in the digestive tract of poultry. Utilization of NSP by microbes will result in short chain fatty acids (SCFA), namely acetic acid, propionate and butyrate which have a positive effect on the digestive tract of poultry. The purpose of this study is to examine changes in levels of rafinose, glucose, mannose, arabinose and sucrose in wheat pollard into a source of functional feed for poultry. The benefit of research is to know the technique / manufacture of functional feed material from wheat pollard. The material used in the research is wheat pollard and aquades by using autoclave tool. The design used was a complete randomized design of 2x3 factorial pattern with 3 replications. The first factor is the duration of steam 30 and 60 minutes while the second factor is the addition of water (0, 30 and 60%). The results showed that the addition of water and the duration of different steam strongly influenced (p <0.001) and had interactions on rafinose, mannose, arabinose, sucrose and glucose parameters. The mean of water addition factor increased rafinose level from 1.11+0.03% to 29+0.02% while steam duration decreased raffinose content from 1.99+0.01% to 1.90+0.04%. Glucose levels increased in water addition factor and steam duration from 0.25+0.01% to 1.06+0.12% and 0.54+0.03% to 0.63+0.07%. The mean of water addition factor decreased the mannose level from 0.19+0.01% to 0.06+0.02% and the steam duration increased the manosa level from 0.09+0.01% to 0.15+0.01%. Levels of arabinose increased in water addition factor and steam duration from 0.30+0.03% to 0.98+0.01% and 0.54+0.02% to 0.70+0.04%. The average water addition decreased the sucrose content from 1.80+0.09% to 1.55+0.04% and the steam duration increased the sucrose content from 1.48+0.04% to 1.72+0.03%. The research conclusions that the steam treatment and the addition of water greatly affect the changes of rafinose, glucose, mannose, arabinose and sucrose in wheat pollard and potentially as functional feed. Recommendations that can be given by researchers is the source of feed ingredients that have high starch content should be processed before it is given to poultry so it has a functional value and improve the digestibility of the feed material.